Validasi SQ-FFQ dengan Estimated Food Record untuk Menilai Asupan Zat Gizi dan Keragaman Pangan pada Mahasiswa - Jesica Yudhis Saputri (Jurnal Ilmu Kesehatan dan Gizi, 2025)
The SQ-FFQ is a commonly used food consumption assessment method because it is quick, relatively inexpensive, simple, and can be self-administered by respondents. Each SQ-FFQ instrument developed should be validated for the target population to avoid overestimation of food consumption measurements. This study aims to determine the validity of the SQ-FFQ instrument as a tool for assessing food consumption. The 3 Days Food Record is used as the gold standard for comparison in the validity of the SQ-FFQ. Sampling was conducted using accidental sampling, with 30 student respondents. The Nutrisurvey application was used to determine the intake of energy, macronutrients, and micronutrients. Meanwhile, for the diversity score, it was based on the IDDS (Individual Dietary Diversity Score) with a score scale of 0-9. Data analysis was performed using SPSS software with Pearson Correlation tests to examine the relationship between the two methods. The correlation coefficient values for all nutrients showed a significance level of <0.005, with the highest correlation coefficient found for energy intake (r=0.708, p<0.001) and the lowest for iron intake (r=0.412, p=0.024). The correlation test for consumption diversity showed a p-value of <0.001 with a correlation coefficient of 0.706, indicating a strong relationship between the SQ-FFQ method and the 3 Days EFR. The results of this study indicate that the SQ-FFQ method is a valid tool for measuring food intake and diversity among university students in Surabaya.